Autologous blood injections for chronic plantar fasciitis – a pilot case-series study shows promising results. (April 2013) - Wheeler, Patrick
Abstract : Objectives: Plantar fasciitis is a common condition with a small number of people having symptoms that are challenging to treat. This prospective case series pilot study paper reports the patient outcomes following ultrasound-guided autologous blood injections (ABI) for the treatment of chronic plantar fasciitis symptoms. Methods and patients: Prospective case-series study of 35 consecutive patients who have undergone ultrasound-guided ABI for recalcitrant plantar fasciitis symptoms in a National Health Service Sports Medicine Clinic in Leicester, UK. Patients treated had suffered with symptoms of plantar fasciitis for an average of more than 4 years pre-ABI. Patients had an average follow-up of 6 months and with a maximum of over 800 days. The outcome measures include visual analogue scale (VAS) for pain, and 7-part patient satisfaction outcome scale. Results: There was an average reduction of VAS of more than 85% post-ABI for all enrolled patients, increasing to nearly 90% in patients with at least 2 months follow-up data. At the latest follow-up appointment 53% of all patients were pain-free following the ABI procedure, increasing to 71% of patients with at least 2 months of follow-up data. Discussion: While causality is not proved in this study design, ultrasound-guided ABI appear to be successful in the treatment of recalcitrant plantar fasciitis. Further studies with greater methodological rigour using a control group or alternative interventions should be conducted.